The Pemanfaatan Limbah Minyak Jelantah Pada Ibu-Ibu Rumah Tangga Di Kelurahan Argasunya Melalui Pembuatan Lilin Aromatherapy Anti Mual Muntah Pada Ibu Hamil: Pemanfaatan Limbah Minyak Jelantah Pada Ibu-Ibu Rumah Tangga Di Kelurahan Argasunya Melalui Pembuatan Lilin Aromatherapy Anti Mual Muntah Pada Ibu Hamil - Hidayah, Fika Nurul; Kulamasary, Diyanah; Widayanti, Wiwin; Gunawan, Ucha Indra; Rahmayani, Shella; Azachra, Akmevi Carissa (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Used cooking oil is household waste which is often thrown away and pollutes the environment, even though it can be used to make goods worth selling, one of which is to make aromatherapy candles which can be used by pregnant women to reduce nausea and vomiting. Argasunya Village is one of the areas in Cirebon City that produces used cooking oil on a large scale, originating from tofu factories. The aim of community service activities is to increase the creativity of housewives so they can utilize used cooking oil waste, have the skills to process used cooking oil into aromatherapy candles. The partner in this service is Argasunya Village, Cirebon City, with 20 PKK women participating. Data collection was carried out in three stages, namely the preparation, implementation and evaluation stages. The activity began with socialization, product making demonstrations, mentoring and the branding and marketing process. Lemon aromatic candles are called Jelita (Jelantah Candle Aromatherapy), one of the uses of which is to relieve or treat nausea and vomiting in pregnant women. This activity was carried out in Argasunya Village with a total of 20 participants. The people of Argasunya Village can use used cooking oil waste to make Aromatherapy Candles.